2022
DOI: 10.1139/cjfr-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timber harvest on epigeous fungal fruiting patterns and community structure in a northern hardwood ecosystem

Abstract: Epigeous fungal fruiting has important impacts on fungal reproduction and ecosystem function. Forest disturbances, such as timber harvest, impact moisture, host availability, and substrate availability, which in turn may drive changes in fungal fruiting patterns and community structure. We surveyed mushrooms in 0.4-ha patch cuts (18 months post-harvest) and adjacent intact hardwood forest in northern New Hampshire, USA, to document the effects of timber harvest on summer fruiting richness, biomass, diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Reported rodent home range sizes are similar to our findings (0.36–2.29 ha; see Appendix S1: Figure S6), suggesting that dispersal by small mammals may on occasion be up to 200 m. Because all target species were frequently captured in both the forest and the harvest gaps, small mammals may play a role in returning forest fungi (particularly AM/ECM taxa), to disturbed areas. This conclusion is bolstered by our finding that macrofungal spore communities did not differ between scat samples collected in forests and harvest gaps, even though previous work from this site indicated that the macrofungal fruiting community itself did differ (Borgmann‐Winter et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Reported rodent home range sizes are similar to our findings (0.36–2.29 ha; see Appendix S1: Figure S6), suggesting that dispersal by small mammals may on occasion be up to 200 m. Because all target species were frequently captured in both the forest and the harvest gaps, small mammals may play a role in returning forest fungi (particularly AM/ECM taxa), to disturbed areas. This conclusion is bolstered by our finding that macrofungal spore communities did not differ between scat samples collected in forests and harvest gaps, even though previous work from this site indicated that the macrofungal fruiting community itself did differ (Borgmann‐Winter et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…To measure spore deposition by wind, we deployed six spore traps at each of the eight study sites for 2 weeks in August 2019. We selected this period to coincide with the approximate peak fruiting of mushrooms (Borgmann‐Winter et al, 2021) and truffles (Stephens et al, 2017) in this region, as well as to capitalize on the occurrence of both early‐ and late‐season fruiters during this period. Spore traps were placed 12 m apart, along a 60 m transect extending 30 m into the harvest gap and 30 m into the forest.…”
Section: Methodsmentioning
confidence: 99%
“…As for seedlings in vitro, a large share of in situ adult mycobiota is not explained by seeds or bulk soil. Contrary to the in vitro experiment, sources of contaminations in situ may be more diverse, including fungi dispersed by wind and small mammals (Zhou et al, 2021;Borgmann-Winter et al), or even plant debris from the litter (Christian et al, 2017). Though fungi may be transmitted by wind (e.g., spores), the low density of plant individuals (in particular H. salicornicum individuals; fertility islands hypothesis) may limit their dispersion and therefore favor the withholding of verticallytransmitted fungi in H. salicornicum leaves, while the mycobiota of belowground tissues are more likely to be influenced by the environment (horizontal transmission).…”
Section: Discussionmentioning
confidence: 99%